Penapisan Penyakit Tidak Menular melalui Pengukuran Kadar Tekanan Darah, Gula Darah dan Kolesterol pada Dewasa Usia Produktif di Jakarta Barat - Shirly Gunawan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes, and dyslipidemia are major global health challenges that contribute to high morbidity and mortality rates. Unhealthy lifestyles, including poor diet, lack of physical activity, and high-stress levels, are key risk factors for NCDs. Early detection through regular screening is essential to prevent complications and improve public health. This community service program aimed to conduct health screenings by measuring blood pressure, blood glucose levels, and cholesterol levels among adults of productive age in West Jakarta. The program also included health education sessions to raise awareness about NCD risk factors and the importance of a healthy lifestyle. Participants underwent blood pressure measurements, random blood glucose tests, and total cholesterol assessments, followed by health counseling and lifestyle modification recommendations. The results emphasized the need for routine health monitoring and preventive interventions to reduce the burden of NCDs in the community.